Solid-Phase Synthesis of Cellulose Acetate Butyrate as Microsphere Wall Materials for Sustained Release of Emamectin Benzoate - Huang, Aimin (Polymers (Basel), 2018)
Emamectin benzoate (EB), a widely used pesticide, is prone to decomposition by ultraviolet light and suffers from the corresponding loss of efficacy. The timed release of EB based on microspheres is one of the effective methods to solve this issue. As a non-toxic cellulose ester, cellulose acetate butyrate (CAB) is regarded as one of the best wall-forming materials for microcapsules with a good controlled release performance. Herein, two methods—mechanical activation (MA) technology and a conventional liquid phase (LP) method—were employed to synthesize different CABs, namely CAB-MA and CAB-LP, respectively. The molecular structure, rheological property, and thermal stability of these CABs were investigated. The two CABs were used to prepare microspheres for the loading and release of EB via an o/w (oil-in-water) solvent evaporation method. Moreover, the performances such as drug loading, drug entrapment, and anti-photolysis of the drug for these microspheres were studied. The results showed that both CABs were available as wall materials for loading and releasing EB. Compared with CAB-LP, CAB-MA presented a lower molecular weight and a narrower molecular weight distribution. Moreover, the MA method endowed the CAB with more ester substituent groups and less crystalline structure in comparison to the LP method, which had benefits including pelletizing and drug loading.